Huangbai Liniment Ameliorates Skin Inflammation in Atopic Dermatitis - Zheng, Ting; Fan, Miao; Wei, Yunbo; Feng, Jinhong; Zhou, Pengcheng; Sun, Xin; Xue, Anqi; Qin, Cheng Xue; Yu, Di (Frontiers in Pharmacology, 2021)
Atopic dermatitis (AD), also known as atopic eczema, is one of the most common skin diseases and is characterized by allergic skin inflammation, redness, and itchiness and is associated with a hyperactivated type 2 immune response. The leading causes of AD include an imbalance in the immune system, genetic predisposition, or environmental factors, making the development of effective pharmacotherapies complex. Steroids are widely used to treat AD; however, they provide limited efficacy in the long term and can lead to adverse effects. Thus, novel treatments that offer durable efficacy and fewer side effects are urgently needed. Here, we investigated the therapeutic potential of Huangbai Liniment (HB), a traditional Chinese medicine, using an experimental AD mouse model, following our clinical observations of AD patients. In both AD patient and the mouse disease model, HB significantly improved the disease condition. Specifically, patients who received HB treatment on local skin lesions (3–4 times/day) showed improved resolution of inflammation. Using the 1-Chloro-2,4-dinitrobenzene (DNCB)-induced AD model in BALB/c mice, we observed that HB profoundly alleviated severe skin inflammation and relieved the itching. The dermatopathological results showed markedly reversed skin inflammation with decreased epidermal thickness and overall cellularity. Correspondingly, HB treatment largely decreased the mRNA expression of proinflammatory cytokines, including IL-1β, TNF-α, IL-17, IL-4, and IL-13, associated with declined gene expression of IL-33, ST2, and GATA3, which are connected to the type 2 immune response. In addition, HB restored immune tolerance by promoting regulatory T (TREG) cells and inhibiting the generation of TH1, TH2, and TH17 cells in vitro and in the DNCB-induced AD mouse model. For the first time, we demonstrate that HB markedly mitigates skin inflammation in AD patients and the DNCB-induced AD mouse model by reinvigorating the T cell immune balance, shedding light on the future development and application of novel HB-based therapeutics for AD.